Respons Masyarakat Digital terhadap Kebijakan Subsidi Kendaraan Listrik Berbasis Anggaran Pendapatan dan Belanja Negara - Rashinta Dwiananda Puteri; Lince Magriasti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The government’s electric vehicle subsidy policy based on the State Budget (APBN) is an effort to support the energy transition and reduce carbon emissions. This study aims to analyze the response of the digital community to this policy through a literature review from various relevant sources. The results of the study show mixed responses. Some community members support this policy because it is seen as capable of promoting the use of environmentally friendly energy and the development of the electric vehicle industry. However, there are also those who criticize the policy because it is considered misdirected and does not prioritize more urgent public needs. Therefore, better transparency and public communication are needed so that this policy can be better accepted by the public.